2022
DOI: 10.1093/hr/uhac137
|View full text |Cite
|
Sign up to set email alerts
|

BoALG10, an α-1,2 glycosyltransferase, plays an essential role in maintaining leaf margin shape in ornamental kale

Abstract: The morphological diversity of leaf margin shapes is an identifying characteristic of many plant species. In our previous work, BoALG10 (α-1,2 glycosyltransferase) was predicted to be a key regulator of leaf margin shape in ornamental kale (Brassica oleracea var. acephala). An alanine and a leucine residues in the conserved domain of the smooth-margined S0835 were substituted by an aspartate and a phenylalanine, respectively, in the corresponding positions of the feathered-margined F0819. However, the expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 46 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…In Brassica oleracea , BoLMI1a , a homolog of LMI1 , was also predicted as the candidate gene regulating leaf lobe formation. In addition, Feng et al [ 34 , 35 ] demonstrated that BoALG10 , which encodes a glycosyltransferase, plays a vital role in leaf lobe development. In Brassica rapa , the physical interval at the distal end of chromosome A10, which is composed of a rich quantitative trait locus (QTL) of the lobed leaf trait, is a research hotspot.…”
Section: Introductionmentioning
confidence: 99%
“…In Brassica oleracea , BoLMI1a , a homolog of LMI1 , was also predicted as the candidate gene regulating leaf lobe formation. In addition, Feng et al [ 34 , 35 ] demonstrated that BoALG10 , which encodes a glycosyltransferase, plays a vital role in leaf lobe development. In Brassica rapa , the physical interval at the distal end of chromosome A10, which is composed of a rich quantitative trait locus (QTL) of the lobed leaf trait, is a research hotspot.…”
Section: Introductionmentioning
confidence: 99%